Analysis of Employee Training Program Implementation in Hotels: Improving Service Quality Through Human Resource Development - Febrianti Mangale; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Al-Qalam Institue, 2025)
This study aims to explore the influence of employee training on service quality at Hotel Lawaka in Ampana City. The method used is a qualitative design with a case study approach, in which data were collected through in-depth interviews, observations, document analysis, and audio-visual documentation. The study's results indicate that employee training at Hotel Lawaka plays a significant role in improving employees' technical skills, professionalism, and work attitudes. Training that involves competent instructors, relevant materials, and interactive methods grounded in hands-on practice enhances service quality and guest satisfaction. Although there are challenges related to employee burnout and limited training, adaptive instructors and tailored training methods that address employees' practical needs have proven effective. This study contributes to the literature on employee training in the hospitality sector and offers practical solutions to improve service quality in hotels with limited resources. The findings also provide recommendations for hotel management to improve employee training programs in a more systematic and structured manner.